2010
DOI: 10.1111/j.2042-3306.2010.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and long‐term follow‐up of 20 horses undergoing surgery for caecal impaction: A retrospective study (2000–2008)

Abstract: Surgery for caecal impaction carries a fair prognosis for a potentially life threatening disease, in particular where caecal dysfunction is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 15 publications
(49 reference statements)
0
18
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Although the quality of care and rate of survival to hospital discharge for horses undergoing colic surgery have increased over the past decades and are now generally considered good, several complications can occur during the immediate postoperative period, which influence short-and long-term outcome. …”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Although the quality of care and rate of survival to hospital discharge for horses undergoing colic surgery have increased over the past decades and are now generally considered good, several complications can occur during the immediate postoperative period, which influence short-and long-term outcome. …”
mentioning
confidence: 99%
“…The option of performing a caecal bypass, by either a jejuno or ileocolostomy was considered. This is usually indicated in horses undergoing surgical treatment for caecal impactions and has a fair overall prognosis (Smith et al 2010). In the present case, however, the sheer weight of the caecum may have resulted in future episodes of colic due to tension on the dorsal mesenteric attachments, together with the potential for external obstruction of other portions of the gastrointestinal tract, due to continued expansion of the lipomatous tissue.…”
Section: Discussionmentioning
confidence: 74%
“…The option of performing a caecal bypass, by either a jejuno or ileocolostomy was considered. This is usually indicated in horses undergoing surgical treatment for caecal impactions and has a fair overall prognosis (Smith et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
“…An example is the prospective multicentre study with long-term follow-up on horses with epiploic foramen entrapment by Archer and others, which showed that overall survival for this condition was just under 80% [13]. Lindegaard and others assessed short-term survival in a similar number of horses with nephrosplenic entrapment of the large colon and found that survival with this condition is considerably higher, at around 90% [14], while a smaller study that is valuable because long-term follow-up is included showed that only 55% of horses treated for caecal impaction survived long term [15]. It is well recognised that having had surgical colic, horses are at increased risk of having colic in future.…”
Section: What Are the Likely Outcomes Associated With Specific Forms mentioning
confidence: 99%